2012
DOI: 10.1007/s00125-012-2543-z
|View full text |Cite
|
Sign up to set email alerts
|

Zinc transporter (ZnT)8186–194 is an immunodominant CD8+ T cell epitope in HLA-A2+ type 1 diabetic patients

Abstract: Aims/hypothesis Anti-zinc transporter (ZnT)8 autoantibodies are commonly detected in type 1 diabetic patients. We hypothesized that ZnT8 is also recognized by CD8+ T cells and aimed at identifying HLA-A2 (A*02:01)-restricted epitope targets. Methods Candidate epitopes were selected by ZnT8 plasmid DNA immunization of HLA-A2/DQ8-transgenic mice and tested for T-cell recognition in peripheral blood mononuclear cells of type 1 diabetic, type 2 diabetic and healthy subjects by IFN-γ enzyme-linked immunospot. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 10 publications
2
55
0
1
Order By: Relevance
“…Parallel ELISpot assays confirmed that ZnT8 186–194 -reactive IFN-γ responses were more frequent in T1D vs. healthy donors (Fig. S8) (7). In contrast, similar frequencies of ZnT8 186–194 and MelanA 26–35 MMr + CD8 + T cells were detected in age-stratified T1D and healthy donors (Fig.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Parallel ELISpot assays confirmed that ZnT8 186–194 -reactive IFN-γ responses were more frequent in T1D vs. healthy donors (Fig. S8) (7). In contrast, similar frequencies of ZnT8 186–194 and MelanA 26–35 MMr + CD8 + T cells were detected in age-stratified T1D and healthy donors (Fig.…”
Section: Resultsmentioning
confidence: 67%
“…Given that ZnT8 186–194 -reactive IFN-γ responses are highly prevalent in T1D patients (7), we started by generating ZnT8 186–194 -reactive CD8 + T-cell clones from a new-onset T1D patient (D222D) (7). Following in-vitro expansion with the ZnT8 186–194 peptide (8), HLA-A2 MMr + cells were labeled with two different fluorochromes (9) and sorted (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Low levels of insulin secretion are detected in many patients even decades after diagnosis: some β cell regeneration occurs after diagnosis, and it has been hypothesized that regeneration may occur during the preclinical stage. efflux transporter ZNT8 (7,(81)(82)(83)(84)(85), chromogranin (86,87), islet-amyloid polypeptide (IAPP) (8), and more. Many are present in secretory granules, and some are unique to β cells (insulin, IGRP, ZNT8), while some are expressed in other cells and tissues, including neuroendocrine cells (GAD65, IA-2) (88,89).…”
Section: T Cells In the Prediabetic Pancreasmentioning
confidence: 99%
“…Several lines of evidence implicate the CD8 T cell lineage in this process: 1) CD8 T cells predominate in islet-centered leukocytic infiltrates close to diagnosis (3,4); 2) autoreactive CD8 T cells with b-cell epitope specificities have been detected in such early infiltrates (3); 3) CD8 T cell clones specific for preproinsulin-derived peptides can kill b-cells in vitro (5,6); and 4) large genetic association studies link disease susceptibility to the inheritance of specific human leukocyte antigen class I (HLAI) alleles (7). This mounting functional and epidemiological evidence, combined with the expanding array of reported HLAI-restricted b-cell epitopes (8,9), provides a strong rationale for detailed studies of autoreactive CD8 T cells in type 1 diabetes.…”
mentioning
confidence: 99%